Partial Block by Riluzole of Muscle Sodium Channels in Myotubes from Amyotrophic Lateral Sclerosis Patients. (7th December 2014) - Deflorio, Cristina; Onesti, Emanuela; Lauro, Clotilde; Tartaglia, Giorgio; Giovannelli, Aldo; Limatola, Cristina; Inghilleri, Maurizio; Grassi, Francesca
Abstract : Denervated muscles undergo fibrillations due to spontaneous activation of voltage-gated sodium (Na + ) channels generating action potentials. Fibrillations also occur in patients with amyotrophic lateral sclerosis (ALS). Riluzole, the only approved drug for ALS treatment, blocks voltage-gated Na + channels, but its effects on muscle Na + channels and fibrillations are yet poorly characterized. Using patch-clamp technique, we studied riluzole effect on Na + channels in cultured myotubes from ALS patients. Needle electromyography was used to study fibrillation potentials (Fibs) in ALS patients during riluzole treatment and after one week of suspension. Patients were clinically characterized in all recording sessions. In myotubes, riluzole (1 μ M, a therapeutic concentration) reduced Na + current by 20%. The rate of rise and amplitude of spikes evoked by depolarizing stimuli were also reduced. Fibs were detected in all patients tested during riluzole treatment and riluzole washout had no univocal effect. Our study indicates that, in human myotubes, riluzole partially blocks Na + currents and affects action potentials but does not prevent firing. In line with this in vitro finding, muscle Fibs in ALS patients appear to be largely unaffected by riluzole.